The Influence of Work Discipline On Employee Performance With Motivation And Job Satisfaction As Intervening Variables In Functional Position Group - Zaahidah, Asmaa; Susita, Dewi; Usman, Osly (Devotion : Journal of Research and Community Service, 2022)
This article discusses how the disparity in office types, which is of interest, affects the performance of First Expert PBC Functional Officers in Indonesia. the degree to which an employee's motivation and work ethic affect their performance. Please use the smart tool in the method that uses structural equation modeling. There were 7 hypotheses, all of which were accepted as significant, with a population of 180 people and a sample size of 124 people. Based on the descriptions in the theoretical framework above, the researcher want to know about work discipline affects employee motivation, Work discipline affects employee job satisfaction, Employee motivation influences employee performance Job satisfaction affects employee performance, Work discipline affects employee performance, Work discipline affects employee performance through motivation to employees, Work discipline influences employee performance through job satisfaction